A taste of Slovene culinary masterpieces with a pinch of contrastive analysis - Stergar, Maja (ELOPE (Ljubljana), 2008)
This paper examines what can be done in the field of food-related terminology (from ingredients to culture-specific dishes) by using contrastive functional analysis as the research methodology. Each language offers different semantic contents to refer to the same referents. The background for the lexico-semantic analysis is investigated and meanings are brought together by studying examples in detail and establishing their functional equivalence.
Keywords: angleščina; contrastive analysis; English; food; gastronomija; leksikologija; lexicology; prevajanje; protistavna analiza; Slovene; Slovene dishes; slovenske jedi; slovenščina; terminologija; translation